THE COMPETITIVENESS OF INDONESIAS EXPORT TO UNITED STATES, 1986-2003: A SHIFT-SHARE ANALYSIS - Fuady, Ahmad Helmy (Universitas Muhammdaiyah Surakarta, 2007)
The objective of this paper is to examine the competitiveness of Indonesias exports to the United States (US) market, compared to other Asian economies, namely Thailand, Malaysia, Singapore, China, Republic of Korea and India, over the period of 1986-2003. A shift-share method is applied to single digit SITC US imports data from those countries. It found that the competitiveness of Indonesias exports changes over time. The Indonesias exports reached its best performance in the period 1992-1997. However, after the 1997 economic crisis, Indonesia faces a serious problem, since none of its export has competitiveness in the US market, compared to the reference economy. The analysis also shows that China has consistently posed a serious pressure not only for Indonesia, but also for the other Asian economies.